PERAN POTENSI LAUT SEBAGAI SEKTOR UNGGULAN DALAM MENINGKATLAN EKONOMI MASYARAKAT DESA ALOR KECIL - Lala Enggadina Moilegi; Clara Desinta Sadu Sally; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This study aims to analyze the role of marine resource potential as a leading sector in driving economic growth and improving the welfare of the community in Alor Kecil Village, Alor Regency. Alor Kecil Village, with its strategic geographical location, possesses significant marine wealth, encompassing fisheries, aquaculture, and marine tourism. Through a qualitative-descriptive approach, this research identifies the most dominant types of marine potential, analyzes their contribution to community income, and formulates optimal development strategies. The results are expected to provide policy recommendations for local and village governments to maximize the utilization of marine potential sustainably.